Analisis Nilai Karakter pada Dongeng Mata Pelajaran Bahasa Indonesia di Sekolah Dasar - Titis Uri Eryuscindy; Alfi Laila; Rian Damariswara (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
This study aims to analyze the character values ​​in Indonesian learning fairy tales in elementary schools which include (1) what types of fairy tales are in elementary school thematic books? (2) what are the character values ​​found in fairy tales in thematic books. The type of research method used in this study was Library Research with the object of research using class I-VI thematic books integrated with the 2013 Curriculum. The data analysis technique used in writing this research was carried out by collecting data, data reduction, data presentation and drawing conclusions. Based on the results of the research, the data obtained are 1) the types of fairy tales in elementary school thematic books there are three types of fairy tales namely types of fable fairy tales which total 29 fairy tales, types of legendary fairy tales which amount to two fairy tales and types of mythical fairy tales which amount to two fairy tales. 2) the character values ​​contained in fairy tales in the integrated thematic books of the 2013 curriculum, there are 15 character values ​​including honesty, tolerance, discipline, hard work, creative, independent, democratic, curiosity, national spirit, respect for achievement, friendly/communicative, love peace, care for the environment, care for social and responsibility